Transformational leadership and measuring emotional intelligence with AHP tool - Nieminen, Jami Johannes (My University, 2020)
This study has two separated goals, the first one is to complete transformational leadership (TL) research from given data. The second one is to generate and test analytical hierarchy process (AHP) measurement for emotional intelligence (EI). In this research, it is shown that how measurements are done and what EI measurements gives, and how to improve it for further research. The research includes theoretical part first and then the empirical part. Theoretical part is focusing on opening TL and its measurement roots. In addition, it shows what EI is and how to measure EI with AHP tool. This research used a qualitative survey to gather TL and EI data. TL research is based on Josu takala’s beforehand gathered data and EI research is based on gathered data. The research results show that TL research was completed successfully, and the data was compatible for another research with same subject. Furthermore, EI research shows that it could be possible to measure EI with AHP but the questionnaire, numerical limits and overall construction of SCM needs more modification and testing.
Keywords: Transformational leadership, Emotional intelligence, AHP tool, measuring with AHP; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management